Peran komunikasi publik dalam menanggapi gelombang disinformasi Covid-19 - Dody Setyawan; Dekki Umamur Ra'is; Abd. Rohman (Universitas Merdeka Malang, 2021)
Disinformation has reduced public confidence in the government and scientists in handling Covid-19. These conditions hamper the overall handling of the Covid-19 pandemic. In the context of responding to a global pandemic, disinformation greatly affects the country's response to a global pandemic by undermining trust, creating fear, and sometimes leading to harmful behavior. It is important for policy makers to understand disinformation and how to respond to it. This study uses a literature review approach with data sources coming from several documents that have been verified and have a relationship with the object of study. The stages of the study start from choosing a review topic, finding and selecting appropriate articles, analyzing and synthesizing the literature, and finally presenting a review of the study. the results show that the government should have official information channels with verified, transparent, sustainable and fast sources of information. The government must also provide clear and definite information through official channels and trusted media. The government must also ensure the consistency of information. In addition, the government must maintain a transparent pattern of communication about the situation, actions and risks it takes. The aim is to restore public trust in public institutions, in information that has been conveyed by the government to the public as well as guidelines that have been provided by the government to the public, such as health protocol guidelines and the last is